Identifying of series resistance and interface states on rhenium/n-GaAs structures using C–V–T and G/ω–V–T characteristics in frequency ranged 50 kHz to 5 MHz - Çiçek, Osman; Durmuş, Haziret; Altındal, Şemsettin (Springer Science and Business Media LLC, 2019)
In this study, Re/n-GaAs with a native oxide layer based on metal–semiconductor (MS) structures were produced and then, the capacitance–voltage–temperature (C–V–T) and the conductance–voltage–temperature (G/ω–V–T) data of them were obtained in the frequency ranged 50 kHz to 5 MHz. Using the raw data, the electronic parameters was calculated by the developed LabVIEW-based program. Methodologically, the series resistance (Rs) values were calculated from the measured capacitance (Cm) and conductivity (Gm) values, while the interface state (Nss) values were obtained from using the combined high (CHF)–low (CLF) frequency capacitance method by Nicollian and Brews. Experimentally, the C values increased with a decreasing frequency, while decreased with increasing temperatures in the depletion and accumulation regions. On the other hand, G/ω values decreased with increasing frequency in forward and reverse bias regions. It can be attributed that, the C and the G/ω values are quite affected by the presence of the Rs and the Nss in the forbidden energy gap and a native oxide layer between M and S. The Rs–V–T curves have especially peaks in accumulation and depletion regions at low frequency values, whereas these peaks decreased at high frequencies. In addition, the Nss–V–T curves give peaks in the range of − 0.1 V to 0.7 V at variable temperatures and the Nss values decrease with increasing temperature and shift towards negative bias regions. Experimental results indicate that the Rs and Nss are important parameters and so, these parameters must be considered in sensor applications based on Re/n-GaAs structures.
Keywords: resistance; conductance–voltage–temperature; G/ω-V-T; rhenium/n-GaAs; interface states; capacitance–voltage–temperature; C-V-T